The buying of lot 37 - Fink, Joseph (Fiction writer); Cranor, Jeffrey, 1975- (Fink, Joseph (Fiction writer). Welcome to Night Vale episodes, 2019)
"From the authors of the New York Times bestselling novels It Devours! and Welcome to Night Vale and the creators of the #1 international podcast of the same name, comes a collection of episodes from Season Three of their hit podcast, featuring an introduction by the authors, a foreword by Dessa, behind-the-scenes commentary, and original illustrations.--